Modeling Exercise Plyometric on Vertical Jump Ability in Football Player Heading - Sitompul, Surya Rezeki; Mahardika, Galang Pakarti; Shiddiq, Hilmi Aziz; Saleh, Muhammad; Pradana, Muhammad Azmi; Karim, Taha Youssef (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study is based on observations made during training at SSB Kabomania Muda Nusantara. It was found that the students had poor heading skills, that the coaches did little plyometric training to increase the explosive power of the leg muscles because the students had poor jumping power, that the training program was not measurable, and that the students were, on average, of short stature. The aim of this study was to investigate the influence of plyometric model exercises, namely different variations of the depth jump and the single-leg jump, on jumping power. The sample consisted of 15 individuals, who were selected using targeted sampling. The research method was a quantitative experiment with a pre-experimental design of one group with pre-test and post-test, i.e., a research design in which one group underwent a pre-test and a post-test. The research results showed that before training with depth jumps and single legs (pre-test), most statistical results were at 42.2, which means that the vertical jumping power of most soccer players was adequate to very poor. After training with depth jumps and single legs (post-test), the statistical value was 57.2, which means that vertical jump power improved to very good. This was confirmed by the t-test, where t > t-table, i.e., 6.91 > 2.14, so the alternative hypothesis (ha) was accepted and the null hypothesis (h0) was rejected. To complete the homogeneous results, further research is needed on the application of the sample group of students with the same average height.